A Matter of Choice: Printed Design Proposals and the Nature of Selection, 1470–1610. (20th November 2018) - Brisman, Shira
Abstract: In the third decade of the sixteenth century, engravers began to frame booklets that offered examples of decorative images and objects with written explanations of their motivations for issuing the proposed designs. Prior to this use of text, earlier engravings by Martin Schongauer and Israhel van Meckenem employed vegetal motifs with severed stems to convey that their compositions were available for selection, drawing an analogy between the utilization of prints by fellow craftsmen and the process of plucking from nature. This vocabulary of extraction returns in the rhymed couplets and playful images of Christoph Jamnitzer's "Neuw Grotteßken Buch" of 1610.